Path following control of an underactuated unmanned marine vehicle with model asymmetry in the presence of ocean current disturbances. (28th August 2019) - Lei, Zhang; Yushan, Sun; Jiayuan, Zhuang; Bo, Wang
Path following control system of an underactuated unmanned marine vehicle is an important guarantee for its successful operation, the path following control problem of an underactuated and asymmetrical unmanned marine vehicle sailing in the presence of ocean current disturbances is addressed. Asymmetry of the unmanned marine vehicle model and higher order velocity coupling terms of damping coefficients of the unmanned marine vehicle are discussed, which would improve the accuracy of the path following control system. A kind of global differential homeomorphism transformation design is proposed to solve the difficulty of nonzero term appearing in the non-diagonal elements of the system inertia coefficient matrix and damping coefficient matrix, which is caused by the model asymmetry of unmanned marine vehicle. An improved line-of-sight guidance algorithm is presented by introducing longitudinal position error and tracking error weight factor into traditional line-of-sight algorithm, which could speed up the path following process, meanwhile the method could be extended to the application of curve path following. Virtual velocity in the tangent direction of the path to be followed is designed for the control system, by increasing a virtual control input, the underactuated control system is simplified, and the higher order velocity coupling terms of damping coefficients are integrated considered in the virtual control law. Stability of the path following control algorithm proposed for unmanned marine vehicle is proved by Lyapunov theory, and some simulation experiments are carried out to verify the effectiveness of the path following control system designed.